Toxic epidermal necrosis associated with afatinib: A case report and literature review - Yang, Wei; Lu, Yansong; Wu, Ze; Niu, Jun (Frontiers in Oncology, 2023)
Objective To report a case of afatinib-induced toxic epidermal necrosis (TEN), in a patient with metastatic non-small cell lung cancer (NSCLC) and compare these findings with that of evaluate similarities and differences to other cases reported in the literature. Methods With use of the algorithm of drug causality for epidermal necrolysis (ALDEN), the effects of afatinib were evaluated in a NSCLC patient who developed TEN. In addition, previous case reports on this topic were included to provide a review of patients’ clinical characteristics, treatment regimens and therapy outcomes in response to afatinib treatment. Results In our case, toxic epidermal necrolysis was observed at five days after afatinib therapy, while other Stevens-Johnson syndrome/toxic epidermal necrolysis responses, as associated with afatinib, did not seem to be induced until a latency period of over thirty days post-afatinib. Treatment with corticosteroids resulted in significant improvements of these clinical symptoms, and eventually to a complete remission. Conclusion Afatinib can result in grade four cutaneous adverse effects like SJS/TEN, with an uncertain latency period. The skin lesions which appear during this period of afatinib treatment should be closely monitored.